(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In education, the term assessment refers to the wide variety of methods or tools that educators use to evaluate, measure, and make note the academic readiness, learning progress, skill acquisition, or educational needs of students. What exactly do we mean when we talk about assessment of student learning? At the course level, assessment provides important data on the breadth and depth of student learning. Assessment is more than grading. It’s about measuring the progress of student learning. Thus, assessment is defined as a “Process of gathering data to better understand the strengths and weaknesses of student learning” (Harris and Hodges, 1995). Assessment for learning (AFL) is an approach to teaching and learning that creates feedback which is then used to improve students’ performance. Students become more involved in the learning process and from this gain confidence in what they are expected to learn and to what standard.